The Effect of Agility Ladder Drill Training in Improving Agility in Volleyball Athletes - Fauzan, Shalman Ahmad; Saputra, Mochamad Yamin; Kusdinar , Yopi; Mulyana, Mulyana (Indonesian Journal of Sport Management, 2024)
One of the factors that influence volleyball is physical condition. This game requires good physical condition, one of which is good agility. In volleyball, players need very high agility to adapt to changing conditions on the field. The researcher aims to examine how significant the agility ladder drill is in increasing the agility of volleyball players. This study uses a quantitative approach with an experimental method and a two-group pretest-posttest research design. The population in this study was PBV Sunrise athletes, the sample used was 30 people aged 17-19 years, the sampling technique used purposive sampling, and the data collection technique used by the researcher was the side step test to find out how fast the sample moved from the right side to the left. The data was processed and analyzed using the normality test with Shapiro-Wilk and then analyzed using a paired t-test with SPSS 25. The T-test value is with a Sig. (2-tailed) value of 0.00, based on the test results, the Sig. Value. (2-tailed) < .05 so that H0 is rejected. It can be concluded that the agility ladder drill significantly affects volleyball players' agility. Thus, routine training using agility ladder drills can be a solution to improve the agility of volleyball players.